Integrating Knowledge from Different Sources for Automatic Back-of-the-book Indexing - Da Sylva, Lyne (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The paper reports research on automatic back-of-the-book indexing. It presents a methodology which brings together knowledge from different disciplines. It is inspired by human indexing methodology and the results are more similar to manually-crafted indexes than those produced by previous automatic approaches. Issues of evaluation and applications are addressed. Cette communication présente les résultats de recherche sur l'indexation automatique de livres. L'étude propose une méthodologie qui rassemble des sources de connaissances provenant de disciplines différentes. La méthodologie s'inspire de l'indexation humaine et les résultats se rapprochent plus de l'indexation manuelle que les autres méthodes d'indexation automatique. Sont également touchés les enjeux d'évaluation et d'applicabilité.